A cross-sectional study of prevalence and correlates of self-harm and suicidal ideation in older adults with dual sensory loss. Issue 1 (January 2022) - Hovaldt, Hanna B.; Crowe, Kathryn; Dammeyer, Jesper
Abstract: Background: Loss of vision and hearing (dual sensory loss: DSL) presents risk factors for self-harm and/or suicidal ideation, although this has rarely been examined for older adults. Objectives: This study estimated the prevalence of thoughts about self-harm and suicide ideation in a national sample of adults with DSL in Denmark. Methods: All 513 people aged 50 years or older who were registered with the national provider of service for people with DSL in Denmark were eligible to participate. Surveys were returned by 290 participants. Participants were mostly female (70%) and aged 50–100 years ( M = 81). Surveys contained questions related to thoughts of self-harm and suicide as well as physical, mental, and social wellbeing. Results: In total, 17% of participants reported thoughts of self-harm and/or suicide in the past two weeks. Not participating in social activities, poorer self-rated health, and presence of more depressive symptoms were associated with self-harm and suicidal ideation. Factors that were associated with self-harm and suicidal ideation were lower levels of emotional support, non-participation in social activities, and symptoms of depression. Conclusions: These finding highlight the importance of ongoing mental health screening and support for older adults with DSL, especially in ensuring accessible mental health services.